Overview of blockchain technology cryptographic security - Nwachukwu, Uchechukwu (My University, 2019)
This thesis work is aimed at developing understanding of the hash functions and algorithms being used in blockchain technologies Bitcoin in comparison to Ethereum and private blockchain hash functions. This study attempts to answer one fundamental research question: “What considerations are important in assessing blockchain cryptographic security, with an emphasis on hash functions”. The study was carried out qualitatively using a desk research approach and combining this approach with using two public blockchains-based cryptocurrencies; Ethereum and Bitcoin as case studies. The research aims to provide a holistic view of blockchain cryptographic security comparing Bitcoin and Ethereum as use cases, and thus providing a consolidated document which students studying cryptography can access to obtain a better understanding of what is involved in blockchain security. From an academic perspective, the research aims at providing a model which can be used in assessing what is important to consider in the cryptographic security of blockchains. Three main categories of factors considered were presented in the proposed model which were strategical factors, complexity attributes and technical drivers. This results in a base crucial metrics such as absence of secret seeds, efficiency of verification, preimage collision resistance, fixed output size, low collision probability, and even distribution of preimages in output.
Keywords: Blockchain, Hash Functions, Digital Signatures, Consensus Algorithms, Bitcoin, Ethereum, Hashing Security Factors